2011
DOI: 10.1123/jsr.20.4.457
|View full text |Cite
|
Sign up to set email alerts
|

Injured Athletes’ Perceptions About Social Support

Abstract: Injury, an unavoidable part of sport, is often accompanied by negative psychological reactions. This reaction may have a negative influence on an athlete's experience of injury and rehabilitation. Findings suggest that perceptions of social support provided by ATCs have the greatest influence on injured athletes' rehabilitation and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
53
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 24 publications
8
53
0
4
Order By: Relevance
“…This also included the perceived ability to be oneself with the coach, as well as the coach's sensitivity to and acceptance of the athlete's own personality, values and choices. These findings are in line with previous research, in which social support from the coach has been perceived as particularly important for athletes' well-being (Clement & Shannon, 2011). Whereas the athletes described characteristics about the coach, satisfaction with the relationship will also be a result of a complex process including both various dimensions of actual support provided as well as the athlete's perception of the support received (Udry, 1997, Wolff et al, 2013.…”
supporting
confidence: 80%
“…This also included the perceived ability to be oneself with the coach, as well as the coach's sensitivity to and acceptance of the athlete's own personality, values and choices. These findings are in line with previous research, in which social support from the coach has been perceived as particularly important for athletes' well-being (Clement & Shannon, 2011). Whereas the athletes described characteristics about the coach, satisfaction with the relationship will also be a result of a complex process including both various dimensions of actual support provided as well as the athlete's perception of the support received (Udry, 1997, Wolff et al, 2013.…”
supporting
confidence: 80%
“…8,9 Growing evidence also suggests that emotional social support, defined as expressions of empathy, love, trust, and caring, 10,11 may be crucial to recovery for injured collegiate athletes; other types of social support, including instrumental support (ie, provision of tangible aid and services) and informational support (ie, provision of advice, suggestions, and information), may be available to injured collegiate athletes as part of injury treatment. 10,11 However, although many universities provide psychological services to their students, including injured student-athletes, the psychologists are not always specially trained in the areas of sport and exercise and may not fulfill the injured athletes' needs. Thus, certified athletic trainers (ATs), who are active in the day-to-day tasks of prevention, recognition, management, and rehabilitation of injuries among athletes, become an important source of emotional social support for injured athletes.…”
mentioning
confidence: 99%
“…Thus, certified athletic trainers (ATs), who are active in the day-to-day tasks of prevention, recognition, management, and rehabilitation of injuries among athletes, become an important source of emotional social support for injured athletes. 11 Advances in sport medicine have reduced the average time required for physical healing from an athletic injury, yet a rapid physical recovery may not provide sufficient time for psychological recovery. Current practices in evaluation and management of injuries address the physical problems underlying an injury and return athletes to full participation as soon as possible, but psychological assessment or care is not usually included.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that student-athletes experience a transition from a primarily athletic identity to a primary academic identity in the two years following an athletic injury (Brewer, Cornelius, Stephan, & Van Raalte, 2010). Social support changes occur for student-athletes following an injury as well, which can result in changes of studentathlete identity (Clement & Shannon, 2011). This social support change may mean the student-athlete starts to interact with other students besides their teammates (e.g.…”
Section: Student-athlete Identitymentioning
confidence: 99%